Soil properties : - Liu, Cheng (Prentice Hall, 1990)
Updated with considerable new and basic material, this fundamental geotechnical (soils) manual provides the reader with the basic theory of soil engineering and over 19 validated accepted experiments commonly used in engineering practice to evaluate properties of soils. This second edition includes new chapters on the description and identification of soils, and the microwave oven technique of determining soil moisture content. Coverage of consolidated undrained testing is also revised and updated.